Motivations to continue teaching for experienced high school agriculture teachers - Ismail, Normala; Smalley, Scott; Mohd Puad, Mohd Hazwan (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The purpose of this study was to understand how different types of motivation (intrinsic, extrinsic, and altruistic) influence experienced high school agriculture teachers who are using the Curriculum for Agricultural Science Education (CASE) to continue teaching. CASE serves as a teaching aid for agriculture teacher to have a better interaction with students in teaching and learning. We applied qualitative research methods in this study by using an open-ended semi-structured interview approach with high school agriculture teacher. In our data collection, we used phone interviews, which were audiotaped and transcribed. Data was coded and member checked. Six themes emerged from this study. These included one major themes (motivations to teach) and five sub-themes (intrinsic motivation, extrinsic motivation, altruistic motivation, teachers’ supports, and curriculum guidance). Nearly, all of the agriculture teachers mentioned intrinsic and altruistic motivations as a primary reason for them to continue teaching in an agricultural education program. From the results, these motivations may affect high school agriculture teacher’s retention. Hence, the study suggested school administrator to enhance agriculture teachers’ motivations by providing full support to a teacher through mentoring, coaching and professional development.